Aromatic amine passivated TiO2 for dye-sensitized solar cells (DSSC) with ~9.8% efficiency. (1st May 2020) - Naveen Kumar, T.R.; Yuvaraj, S.; Kavitha, P.; Sudhakar, Vediappan; Krishnamoorthy, Kothandam; Neppolian, B.
Graphical abstract: Highlights: Aromatic amines namely aniline and o-phenylenediamine capped TiO2 was synthesized. The life time of o-phenylenediamine/TiO2 (T-2) composite was measured as 9.8 ms. Photo-conversion efficiency of T-2 composite was found to be 9.84%. Abstract: In this work, the efficiency of dye-sensitized solar cells (DSSC) was improved by capping TiO2 with simple aromatic amines as a complexing agent. The aromatic amines, aniline and o-phenylenediamine capped TiO2 composites were synthesized via hydrothermal route and used as scattering layer in dye-sensitized solar cell (DSSC). Markedly, the maximum photo-conversion efficiency of 9.84% was achieved with o-phenylenediamine capped-TiO2 composite as o-phenylenediamine capped-TiO2 showed higher reflectivity than the pristine TiO2, which is highly beneficial for reflecting the photons back to photoanode. In addition, the average life time of carriers in o-phenylenediamine capped-TiO2 was found to be 9.8 ms, which was 2 times higher than the pristine TiO2 (4.29 ms).